Polycystic ovary syndrome: early detection in the adolescent - Jeffrey Chang, R; Coffler, Mickey S (Clinical obstetrics and gynecology, 2007)
The primary clinical manifestations of polycystic ovary syndrome (PCOS) are hirsutism and irregular menstrual bleeding due to ovarian androgen excess and chronic anovulation. Historically, these features emerge late in puberty or shortly thereafter. The presence of insulin resistance or obesity, both commonly associated with this disorder, seems to further amplify the severity of the presentation. Perhaps, the most important finding is that of progressive hirsutism. Irregular menstrual bleeding is less reliable unless the duration of menstrual irregularity is persistent. However, mild hair growth and chronic anovulation are also regarded as normal components of the late stages of puberty and early adolescence and may persist for several years. It is for this reason that the diagnosis is often not made until later in life when endocrine and metabolic dysfunctions have been firmly established. The evolution of PCOS during early adolescence is not well-understood, but seems to involve abnormal activation of the hypothalamic-pituitary-ovarian-adrenal axis accompanied by specific morphologic changes of the ovary. Efforts to minimize the clinical features of PCOS in young adolescent girls depend on early diagnosis and timely suppression of excess ovarian androgen production.